ANALISIS RESEPSI KARAKTER PEREMPUAN DALAM FILM MARLINA SI PEMBUNUH DALAM EMPAT BABAK - Atria Sakinah Putri; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Media construction tends to display female characters that are complex and contradictory. Often negative stereotypes about the character of women are displayed in a weak position and their existence is always exploited by the media as a sweetener object. However, it cannot be denied that patriarchal culture is very much inherent in labeling subordinate women. This film tells about the struggle of a female character named Marlina. He did not stay silent watching his livestock being taken by robbers who also wanted to claim his honor. Marlina defended herself by killing the robbers and beheading one of the robbers to be taken to the police station as evidence of justice. This study aims to see how the informants interpret the female characters in the film Marlina The Killer in Four.This research uses descriptive qualitative research that focuses on reception. The research data were obtained through a process of interviews, observation and documentation of the determination of informants using purposive sampling techniques. The data analysis technique used is the reception analysis method which consists of data collection, analysis and interpretation of reception data. While the technique of checking the validity of the data uses source triangulation.The results of this study indicate that the majority of informants are in the dominant position to hold a reception resulting in the character of women helping each other, intelligent, firm, strong, brave, good, weak, and emotional. While the informants who are in the negotiating position perceive the female character as strong but dangerous, smart but do not like the act of murder, brave but may have become a habit. Then the informant who is in the position of opposition perceives the characters of gossiping, creepy, selfish, and emotional women. Keyword: Reception Analysis, Women’s Character, Film